ЖОҒАРЫ ӨНІМДІ АЗОТСІҢІРЕТІН КЕҢ СПЕКТРЛІ БЕЙІМДЕЛГІШ СИМБИОЗДЫ ӨСІМДІК-МИКРОБТЫ ЖҮЙЕНІ ТАҢДАП АЛУ ТЕХНОЛОГИЯСЫ (Experimental biology, 2017)
The Study of the influence of biological preparation "Nitragin" on the base of shtumms S. meliloty for lucence seeds productivity and ecological condition of soil.
Keywords: Nitragin; soil